EFFECT OF EDUCATION LEVEL AND WORK ENVIRONMENT ON EMPLOYEE PRODUCTIVITY IN PT.TESO INDAH INDRAGIRI HULU REGENCY - Ivalaina Astarina; Angga Hapsila; Gilang Ramadan (JURNAL MANAJEMEN DAN BISNIS, 2020)
The study will determine the effect of education and environment work in simultaneous and partial towards productivity employee PT Teso Beautiful Regency Indragiri Hulu. Research is using the data primary data and secondary by spreading the questionnaire to 45 samples were selected, the authors undertake the processing of data by clicking using linear regression multiple that process by using SPSS (statistical package for social science ) version 21 to obtain the output in order to conclude the results this research. From the research results can be drawn a simultaneous conclusion, there is influence significantly between levels of education and environmental work on employees' productivity. A partial level of education affects productivity and environmental work, and the partial impact significantly on employees' productivity.